Training on Making and Developing Learning Video Media Using Software Wondershare Filmora Against the History Teacher of SMA Negeri 3 Palu - Carles Kapile; Nuraedah Nuraedah; Fajar Nugroho (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Online learning implemented at SMA Negeri 3 Palu requires every teacher to change and innovate in their learning strategies, the use of appropriate media and support for online learning will determine the success of students' learning. The implementation of community service aims to provide knowledge to history teachers at SMA Negeri 3 Palu regarding the creation and development of learning video media using Wondershare Filmora software. This service activity was attended by history teachers and students, they were very enthusiastic in participating in service activities. The output produced is a learning video media developed by a history teacher that is in accordance with the direction and guidance of the service team with suggestions and input from students regarding interesting media to use in online learning.